Positive electrode sheet and preparation method thereof and hybrid ion battery
By designing a multi-layer structure in the positive electrode sheet of the potassium ion battery, including a potassium-containing active material layer and a lithium-containing active material layer, combined with the use of polymers, the challenges of potassium ion battery in terms of energy density and cycle life are solved, and the challenges of potassium ion battery are achieved. High energy density and good cycle performance.
Patent Information
- Application Number
- CN202411429169.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-14
Smart Images

Figure CN118943292B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet and a preparation method thereof, and a hybrid ion battery. Background Art
[0002] Potassium and lithium have similar standard redox potentials, but potassium has abundant reserves in the earth's crust (1.5wt%), which leads to low cost of potassium ion batteries. At the same time, potassium ions have fast ion transport kinetics in electrolytes, which makes potassium ion batteries have excellent prospects, so potassium ion batteries have been rapidly developed. Currently, the positive electrode materials that can be used for potassium ion batteries are mainly divided into polyanion, Prussian blue, organic positive electrode materials and layered transition metal oxide positive electrode materials. Layered transition metal oxide (A x MO 2 , A=K, M=V, Mn, Fe, Ni, Cr, Co, etc. and their combinations) are widely used due to their stable framework structure, simple synthesis method, high output voltage and high commercial feasibility.
[0003] Current potassium-ion batteries still face major challenges in terms of energy density and cycle life, including narrow voltage window, electrode dissolution, corrosion, and unexpected byproducts. These fundamental problems can lead to irreversible capacity loss, poor cycle stability, and short circuits, severely limiting the development of potassium-ion batteries. + Effective storage. Therefore, it is necessary to further improve its cycle performance and energy density to meet actual needs. Usually, the means to improve energy density are mainly to increase voltage and capacity. Since the layered oxide of the positive electrode of the potassium ion battery has poor air stability, the surface of the material is prone to breakage during the cycle, and side reactions occur after contact with the electrolyte, consuming active potassium, which leads to poor cycle performance and further limits its application. For example, CN113675394A discloses a potassium ion battery positive electrode sheet, which includes aluminum foil and an active material layer coated on the aluminum foil, the active material layer includes an active material, a conductive agent and a binder, and the molecular formula of the active material is: K x Mn y Cu 1-y-z Sb z O 2 (KMCSO), x, y, and z are the atomic numbers respectively. Since the positive electrode cannot prevent the material from being corroded by air during use, there are certain disadvantages. Summary of the invention
[0004] In view of this, the present invention provides a positive electrode sheet and a preparation method thereof and a hybrid ion battery. The positive electrode sheet can effectively avoid being corroded by air and has the characteristics of high energy density and good cycle performance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a positive electrode sheet, which includes:
[0007] A positive electrode current collector;
[0008] A first active material layer disposed on at least one surface in the thickness direction of the positive electrode current collector; the first active material layer includes a first active material, a first conductive agent, and a binder, and the first active material is a potassium-containing active material;
[0009] A second active material layer disposed on the surface of the first active material layer away from the positive electrode current collector; the second active material layer includes a second active material, a second conductive agent, and a polymer, and the second active material is a lithium-containing active material.
[0010] In an embodiment of the present invention, the polymer includes at least one of polyvinyl alcohol and polyvinylpyrrolidone.
[0011] In an embodiment of the present invention, the chemical general formula of the first active material is KNi w Fe v Mn m O 2 , where 0 < w ≤ 0.4, 0 < v ≤ 0.6, 0 < m ≤ 0.6, and w + v + m = 1.
[0012] In an embodiment of the present invention, the chemical general formula of the second active material is LiNi x Co y Mn z O 2 , where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1.
[0013] Preferably, the molar ratio of the first active material to the second active material is (1~11):1.
[0014] Preferably, the molar ratio of the second active material to the polymer is (200~1250):1.
[0015] Preferably, the mass ratio of the first active material, the first conductive agent, and the binder in the first active material layer is (5~10):1:(0.05~0.07).
[0016] Preferably, the mass ratio of the second active material, the second conductive agent, and the polymer in the second active material layer is (4~8):1:(5~20).
[0017] Preferably, the thickness of the first active material layer is 0.1~2 mm.
[0018] Preferably, the second active material layer has a thickness of 0.1 to 2 mm.
[0019] In an embodiment of the present invention, a first projection of the first active material layer in the thickness direction of the positive electrode current collector coincides with a second projection of the second active material layer in the thickness direction of the positive electrode current collector, and the area of the first projection is equal to the area of the second projection.
[0020] In an embodiment of the present invention, the first conductive agent and the second conductive agent independently include at least one of conductive carbon black, acetylene black, graphene, conductive graphite, conductive carbon tubes, and conductive carbon fibers.
[0021] In an embodiment of the present invention, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose.
[0022] In a second aspect, the present invention provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:
[0023] S1, mixing a first active material, a first conductive agent, a binder, and a first solvent uniformly to obtain slurry A;
[0024] The second active material, the second conductive agent and the second solvent are mixed evenly to obtain slurry B. 1 ; Mix the polymer and the third solvent, and heat and stir to obtain a polymer solution; slurry B 1 Mix evenly with the polymer solution to obtain slurry B 2 ;
[0025] S2, coating the slurry A on the surface of the positive electrode current collector, and performing a first drying to obtain a pole piece composited with a first active material layer;
[0026] Slurry B 2 The positive electrode is coated on the surface of the electrode sheet compounded with the first active material layer, and then subjected to a second drying, a rolling press, and a third drying to obtain a positive electrode sheet.
[0027] Preferably, the temperature of the first drying is 80-120° C., and the time of the first drying is 1-3 hours.
[0028] Preferably, the temperature of the second drying is 80-120° C., and the time of the second drying is 1-3 hours.
[0029] Preferably, the temperature of the third drying is 80-120° C., and the time of the third drying is 20-30 hours.
[0030] In a third aspect, the present invention provides a hybrid ion battery, which comprises the above-mentioned positive electrode sheet, and / or the positive electrode sheet prepared by the above-mentioned preparation method.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The positive electrode sheet of the present invention is provided with a second active material layer including a lithium-containing active material and a polymer on the surface of the potassium-containing active material layer. Among them, due to the presence of the polymer, on the one hand, the potassium-containing positive electrode active material can be prevented from being corroded by the air, thereby preventing capacity loss. On the other hand, it can also effectively prevent the electrolyte solvent from contacting the broken positive electrode during the cycle process, thereby avoiding the occurrence of side reactions and improving the cycle performance. At the same time, due to the presence of the lithium-containing active material, lithium and potassium ions have a synergistic effect, which can improve the cycle performance while also improving the energy density. Therefore, the positive electrode sheet of the present invention effectively improves the problem that traditional potassium ion battery materials are easily corroded by air, thereby losing active potassium, and having poor capacity and cycle performance, and has the characteristics of high energy density and good cycle performance.
[0033] (2) Compared with other methods of doping lithium at the material level and performing multi-step blending during the homogenization or coating process, the preparation method of the present invention simplifies the coating process and improves manufacturability because the polymer and the lithium-containing active material are mixed during the homogenization process. The preparation method is simpler and more efficient. At the same time, since the polymer has the function of a binder, no additional binder needs to be added to the second active material layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the structure of the positive electrode sheet of the present invention, wherein 1 represents the current collector, 2 represents the first active material layer, and 3 represents the second active material layer. DETAILED DESCRIPTION
[0035] The present invention discloses a positive electrode sheet and a method for preparing the same and a hybrid ion battery. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0036] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0037] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0038] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0039] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0040] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0041] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0042] Specifically, the present invention adopts the following technical solutions:
[0043] In a first aspect, the present invention provides a positive electrode sheet, the positive electrode sheet comprising:
[0044] Positive electrode current collector;
[0045] A first active material layer, the first active material layer is disposed on at least one surface of the positive electrode current collector in the thickness direction; the first active material layer comprises a first active material, a first conductive agent and a binder, and the first active material is an active material containing potassium;
[0046] The second active material layer is arranged on the surface of the first active material layer away from the positive electrode current collector; the second active material layer comprises a second active material, a second conductive agent and a polymer, and the second active material is a lithium-containing active material.
[0047] In the embodiments of the present invention, the polymer includes at least one of polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP).
[0048] Preferably, the molecular weight of the polymer is from 10,000 to 2,000,000. Exemplarily, the molecular weight of the polymer is any value among 10,000, 50,000, 75,000, 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1,000,000, 1,500,000, 2,000,000 or any value within the range formed by any two of the above values.
[0049] In the embodiments of the present invention, the chemical general formula of the first active substance is KNi w Fe v Mn m O 2 , where 0 < w ≤ 0.4, 0 < v ≤ 0.6, 0 < m ≤ 0.6, and w + v + m = 1. Exemplarily, the first active substance includes, but is not limited to, KNi 0.33 Fe 0.33 Mn 0.33 O 2 , KNi 0.3 Fe 0.3 Mn 0.4 O 2 , KNi 0.2 Fe 0.6 Mn 0.2 O 2 , KNi 0.1 Fe 0.6 Mn 0.3 O 2 , KNi 0.4 Fe 0.1 Mn 0.5 O 2 , KNi 0.1 Fe 0.3 Mn 0.6 O 2 and so on.
[0050] In the embodiments of the present invention, the chemical general formula of the second active substance is LiNi x Co y Mn z O 2 , where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1. Exemplarily, the second active substance includes, but is not limited to, LiNi 0.33 Co 0.33 Mn 0.33 O 2 , LiNi 0.8 Co 0.1 Mn0.1 O 2 、LiNi 0.1 Co 0.8 Mn 0.1 O 2 、LiNi 0.1 Co 0.1 Mn 0.8 O 2 、LiNi 0.2 Co 0.4 Mn 0.4 O 2 、LiNi 0.5 Co 0.3 Mn 0.2 O 2 etc.
[0051] Preferably, the molar ratio of the first active substance to the second active substance is (1-11): 1. Exemplarily, the molar ratio of the first active substance to the second active substance is any value among 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, or any value within the range of any two of the above values.
[0052] Preferably, the molar ratio of the second active substance to the polymer is (200-1250): 1. Exemplarily, the molar ratio of the second active substance to the polymer is any value among 200: 1, 250: 1, 300: 1, 400: 1, 450: 1, 500: 1, 600: 1, 700: 1, 750: 1, 800: 1, 900: 1, 1000: 1, 1100: 1, 1200: 1, 1250: 1, or any value within the range consisting of any two of the above values.
[0053] Preferably, the mass ratio of the first active material, the first conductive agent, and the binder in the first active material layer is (5-10):1:(0.05-0.07). Exemplarily, the mass ratio of the first active material, the first conductive agent, and the binder in the first active material layer is any value among 9.8:1:0.06, 5:1:0.06, 5.3:1:0.06, 5:1:0.07, 10:1:0.05, or any value within the range of any two of the above values.
[0054] Preferably, the mass ratio of the second active material, the second conductive agent, and the polymer in the second active material layer is (4-8):1:(5-20). Exemplarily, the mass ratio of the second active material, the second conductive agent, and the polymer in the second active material layer is any value among 4.8:1:20, 4.9:1:9.4, 4.7:1:5.5, 6.8:1:6, 7.2:1:5, 6.7:1:20, 4:1:20, 8:1:5, or any value within the range of any two of the above values.
[0055] Preferably, the thickness of the first active material layer is 0.1 to 2 mm. Exemplarily, the thickness of the first active material layer is any value among 0.1 mm, 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2 mm, or any value within the range of any two of the above values.
[0056] Preferably, the thickness of the second active material layer is 0.1 to 2 mm. Exemplarily, the thickness of the second active material layer is any value among 0.1 mm, 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2 mm, or any value within the range of any two of the above values.
[0057] In an embodiment of the present invention, a first projection of the first active material layer in the thickness direction of the positive electrode current collector coincides with a second projection of the second active material layer in the thickness direction of the positive electrode current collector, and the area of the first projection is equal to the area of the second projection.
[0058] In an embodiment of the present invention, the first conductive agent and the second conductive agent independently include at least one of conductive carbon black, acetylene black, graphene, conductive graphite, conductive carbon tubes, and conductive carbon fibers.
[0059] In an embodiment of the present invention, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose.
[0060] In a second aspect, the present invention provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:
[0061] S1, mixing a first active material, a first conductive agent, a binder, and a first solvent uniformly to obtain slurry A;
[0062] The second active material, the second conductive agent and the second solvent are mixed evenly to obtain slurry B. 1 ; Mix the polymer and the third solvent, and heat and stir to obtain a polymer solution; slurry B1 Mix evenly with the polymer solution to obtain slurry B 2 ;
[0063] S2, coating the slurry A on the surface of the positive electrode current collector, and performing a first drying to obtain a pole piece composited with a first active material layer;
[0064] Slurry B 2 The positive electrode is coated on the surface of the electrode sheet compounded with the first active material layer, and then subjected to a second drying, a rolling press, and a third drying to obtain a positive electrode sheet.
[0065] In an embodiment of the present invention, the first solvent and the second solvent are independently organic solvents, such as N-methylpyrrolidone (NMP).
[0066] In an embodiment of the present invention, the third solvent is water.
[0067] In an embodiment of the present invention, slurry A and slurry B 1 The solid content is a conventional solid content, for example, 40% to 80%, and the present invention is not specifically limited here.
[0068] In an embodiment of the present invention, the mass volume ratio of the polymer to the third solvent is (1-5) in g / mL: 100. Exemplarily, the mass volume ratio of the polymer to the third solvent is any value among 1:100, 1:50, 3:100, 1:25, 1:20 or any value within the range consisting of any two of the above values.
[0069] Preferably, the temperature of heating and stirring in step S1 is 80-98° C. and the time is 1-2 hours. Heating and stirring are conventional techniques and are not specifically limited in the present invention.
[0070] As a preference, slurry B 1 Mix the polymer solution evenly: After the polymer solution is cooled to 40-50°C, add slurry B dropwise 1 Mix well.
[0071] Preferably, the temperature of the first drying is 80-120°C, and the time of the first drying is 1-3 hours. Exemplarily, the temperature of the first drying is any value among 80°C, 90°C, 100°C, 110°C, 120°C, or any value within the range of any two of the above values, and the time of the first drying is any value among 1 h, 1.5 h, 2 h, 2.5 h, 3 h, or any value within the range of any two of the above values.
[0072] Preferably, the temperature of the second drying is 80-120°C, and the time of the second drying is 1-3 hours. Exemplarily, the temperature of the second drying is any value among 80°C, 90°C, 100°C, 110°C, 120°C, or any value within the range of any two of the above values, and the time of the second drying is any value among 1 h, 1.5 h, 2 h, 2.5 h, 3 h, or any value within the range of any two of the above values.
[0073] Preferably, the temperature of the third drying is 80-120°C, and the time of the third drying is 20-30h. Exemplarily, the temperature of the third drying is any value among 80°C, 90°C, 100°C, 110°C, 120°C, or any value within the range of any two of the above values, and the time of the third drying is any value among 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h, 30 h, or any value within the range of any two of the above values.
[0074] In a third aspect, the present invention provides a hybrid ion battery, which comprises the above-mentioned positive electrode sheet, and / or the positive electrode sheet prepared by the above-mentioned preparation method.
[0075] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.
[0076] The present application has no particular restrictions on the negative electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.
[0077] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.
[0078] The present invention will be further described below in conjunction with embodiments:
[0079] Embodiment 1:
[0080] (1) 11.72 g of active material (KNi 0.33 Fe 0.33 Mn 0.33 O 2 , 0.09 mol), 1.2 g of conductive agent carbon black (Super-P) and 0.07 g of binder polyvinylidene fluoride (PVDF) are uniformly dispersed in solvent N-methylpyrrolidone (NMP) and mixed to prepare slurry A.
[0081] Among them, in slurry A, the active material (KNi 0.33 Fe 0.33 Mn 0.33 O 2), the mass ratio of conductive agent and adhesive is 9.8:1:0.06.
[0082] (2) 0.72 g of active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 , 0.008 mol), 0.15 g of conductive agent carbon black (Super-P) were uniformly dispersed in solvent N-methylpyrrolidone (NMP) and mixed to prepare slurry B 1 ; Dissolve 3g PVA (0.00004mol) in 100mL deionized water, stir at 98℃ for 2h until clear, cool to 45℃, and add slurry B dropwise under continuous stirring. 1 , stirring continued for 15 min to obtain slurry B 2 .
[0083] Among them, slurry B 2 Among them, the active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ), the mass ratio of conductive agent and PVA is 4.8:1:20;
[0084] Active substances (KNi 0.33 Fe 0.33 Mn 0.33 O 2 ) and active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) has a molar ratio of 11:1;
[0085] Active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) and PVA in a molar ratio of 200:1.
[0086] (3) Slurry A was evenly coated on the aluminum foil current collector and the coating was dried at a temperature of 100°C for 2 h. The coating thickness of slurry A was 0.1 mm.
[0087] (4) Slurry B 2 Evenly apply it on the coating obtained in step (3), and dry the coating at a temperature of 100°C for 2 hours. 2 The coating thickness is 0.1 mm. After rolling the coating, a composite electrode is obtained, which is baked in a vacuum drying oven at 80°C for 24 hours to obtain a positive electrode with a structure as shown below: Figure 1 shown.
[0088] (5) Preparation of hybrid ion batteries:
[0089] The positive electrode sheet was cut into 12 mm round positive electrode sheets using a cutting machine. A potassium metal sheet with a diameter of 14 mm and a thickness of 0.2 mm was used as the negative electrode, a 0.1 mol / L potassium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte (the volume ratio of ethylene carbonate to dimethyl carbonate was 1:1), and a Whatman GF / F glass fiber with a diameter of 16 mm was used as the separator. The CR2032 button battery was assembled in a glove box filled with high-purity argon.
[0090] Embodiment 2:
[0091] The only difference between this embodiment and embodiment 1 is that: slurry B 1 Active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) was added in an amount of 1.58 g (0.018 mol), and the amount of conductive agent carbon black (Super-P) was added in an amount of 0.32 g;
[0092] Among them, slurry B 2 Among them, the active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ), the mass ratio of conductive agent and PVA is 4.9:1:9.4;
[0093] Active substances (KNi 0.33 Fe 0.33 Mn 0.33 O 2 ) and active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) has a molar ratio of 5:1;
[0094] Active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) and PVA have a molar ratio of 450:1.
[0095] Embodiment 3:
[0096] The only difference between this embodiment and embodiment 1 is that: slurry B 1 Active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2) was added in an amount of 2.6 g (0.03 mol), and the amount of conductive agent carbon black (Super-P) was added in an amount of 0.55 g;
[0097] Among them, slurry B 2 Among them, the active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ), the mass ratio of conductive agent and PVA is 4.7:1:5.5;
[0098] Active substances (KNi 0.33 Fe 0.33 Mn 0.33 O 2 ) and active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) has a molar ratio of 3:1;
[0099] Active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) and PVA has a molar ratio of 750:1.
[0100] Embodiment 4:
[0101] The only difference between this embodiment and embodiment 1 is that: slurry B 1 Active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) was added in an amount of 3.4 g (0.04 mol), and the conductive agent carbon black (Super-P) was added in an amount of 0.5 g;
[0102] Among them, slurry B 2 Among them, the active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ), the mass ratio of conductive agent and PVA is 6.8:1:6;
[0103] Active substances (KNi 0.33 Fe 0.33 Mn 0.33 O 2 ) and active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) has a molar ratio of 2.3:1;
[0104] Active material (LiNi0.33 Co 0.33 Mn 0.33 O 2 ) and PVA have a molar ratio of 1000:1.
[0105] Embodiment 5:
[0106] The only difference between this embodiment and embodiment 1 is that: slurry B 1 Active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) was added in an amount of 4.3 g (0.05 mol), and the amount of conductive agent carbon black (Super-P) was added in an amount of 0.6 g;
[0107] Among them, slurry B 2 Among them, the active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ), the mass ratio of conductive agent and PVA is 7.2:1:5;
[0108] Active substances (KNi 0.33 Fe 0.33 Mn 0.33 O 2 ) and active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) has a molar ratio of 1.8:1;
[0109] Active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) and PVA have a molar ratio of 1250:1.
[0110] Embodiment 6:
[0111] The only difference between this embodiment and embodiment 1 is that: slurry B 1 Active material uses LiNi 0.8 Co 0.1 Mn 0.1 O 2 , the amount added is 1g (0.02 mol);
[0112] Among them, slurry B 2 Among them, the active material (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), the mass ratio of conductive agent and PVA is 6.7:1:20;
[0113] Active substances (KNi 0.33 Fe 0.33 Mn 0.33 O 2 ) and active material (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) has a molar ratio of 4.5:1;
[0114] Active material (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) and PVA have a molar ratio of 500:1.
[0115] Embodiment 7:
[0116] The only difference between this embodiment and embodiment 1 is that the active material of slurry A is KNi 0.3 Fe 0.3 Mn 0.4 O 2 , the amount added is 5.87 g (0.05 mol);
[0117] In slurry A, the active material (KNi 0.3 Fe 0.3 Mn 0.4 O 2 ), the mass ratio of conductive agent to binder is 5:1:0.06;
[0118] Active substances (KNi 0.3 Fe 0.3 Mn 0.4 O 2 ) and active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) has a molar ratio of 6.3:1.
[0119] Embodiment 8:
[0120] The only difference between this embodiment and embodiment 1 is that the active material of slurry A is KNi 0.2 Fe 0.6 Mn 0.2 O 2 , the amount added is 6.4 g (0.05 mol);
[0121] In slurry A, the active material (KNi 0.2 Fe 0.6 Mn 0.2 O 2), the mass ratio of conductive agent to binder is 5.3:1:0.06;
[0122] Active substances (KNi 0.2 Fe 0.6 Mn 0.2 O 2 ) and active material (LiNi 0.33 Co 0.33 Mn 0.33 O 2 ) has a molar ratio of 6.3:1.
[0123] Embodiment 9:
[0124] The only difference between this embodiment and embodiment 1 is that the polymer PVA in step (2) is replaced by polyvinyl pyrrolidone (PVP).
[0125] Comparative Example 1:
[0126] (1) 7.5 g of active substance (KNi 0.33 Fe 0.33 Mn 0.33 O 2 ), 1.5 g of conductive agent carbon black (Super-P) and 0.07 g of binder polyvinylidene fluoride (PVDF) are uniformly dispersed in solvent N-methylpyrrolidone (NMP) and mixed to prepare slurry A.
[0127] (2) Slurry A is evenly coated on the coating obtained in step (2), and the coating is dried at a temperature of 80°C for 2 hours. The coating is rolled to obtain a composite electrode, which is then baked in a vacuum drying oven at 80°C for 24 hours to obtain a positive electrode.
[0128] (3) Preparation of hybrid ion batteries:
[0129] The positive electrode sheet was cut into 12 mm round positive electrode sheets using a cutting machine. A potassium metal sheet with a diameter of 14 mm and a thickness of 0.2 mm was used as the negative electrode, a 0.1 mol / L potassium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte (the volume ratio of ethylene carbonate to dimethyl carbonate was 1:1), and a Whatman GF / F glass fiber with a diameter of 16 mm was used as the separator. The CR2032 button battery was assembled in a glove box filled with high-purity argon.
[0130] Performance Testing
[0131] Use constant current charge and discharge mode to perform charge and discharge tests at a current density of 0.1C. Test items include:
[0132] (1) 0.1C first cycle discharge capacity:
[0133] First cycle discharge capacity test: The hybrid ion battery was placed at 25°C for 30 minutes, charged to 4V at 0.1C constant current, then charged to 0.05C at constant voltage, and then discharged to 1.5V at 0.1C constant current. The discharge capacity at this time was recorded as the first cycle discharge capacity.
[0134] (2) 1 C 100 cycles capacity retention rate:
[0135] Cycle performance test: The hybrid ion battery was placed at 25°C for 30 minutes, charged at 1C constant current to 4V, then charged at constant voltage to 0.05C, and then discharged at 1C constant current to 1.5V. The discharge capacity at this time was recorded as the discharge capacity of the first cycle. The battery was placed at 25°C for 10 minutes, and the capacity of the hybrid ion battery at the 100th cycle was recorded.
[0136] The test results are shown in Table 1 below.
[0137] Table 1
[0138]
[0139] It can be seen from the data in Table 1 that the positive electrode sheets prepared in Examples 1-9 of the present invention have better discharge capacity and capacity retention rate during the charge and discharge process than those in Comparative Example 1. Among them, the positive electrode sheet prepared in Example 5 has better electrical performance.
[0140] In summary, the positive electrode sheet prepared by the present invention can significantly improve the capacity and cycle performance of traditional potassium ion batteries.
[0141] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises: Positive electrode current collector; The first active material layer, the first active material layer is disposed on at least one surface in the thickness direction of the positive current collector; the first active material layer includes a first active material, a first conductive agent, and a binder, the first active material is a potassium-containing active material; the chemical general formula of the first active material is KNi w Fe v Mn m O2, where 0 < w ≤ 0.4, 0 < v ≤ 0.6, 0 < m ≤ 0.6, and w + v + m = 1; The second active material layer is disposed on the surface of the first active material layer away from the positive current collector; the second active material layer includes a second active material, a second conductive agent, and a polymer, and the second active material is a lithium-containing active material; the chemical general formula of the second active material is LiNi x Co y Mn z O2, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1; the polymer includes at least one of polyvinyl alcohol and polyvinylpyrrolidone.
2. The positive electrode sheet according to claim 1, characterized in that: The molar ratio of the first active substance to the second active substance is (1-11):
1.
3. The positive electrode sheet according to claim 1, characterized in that: The molar ratio of the second active substance to the polymer is (200-1250):
1.
4. The positive electrode sheet according to claim 1, characterized in that: The mass ratio of the first active material, the first conductive agent, and the binder in the first active material layer is (5-10):1:(0.05-0.07).
5. The positive electrode sheet according to claim 1, characterized in that: The mass ratio of the second active material, the second conductive agent, and the polymer in the second active material layer is (4-8):1:(5-20).
6. The positive electrode sheet according to claim 1, characterized in that: The thickness of the first active material layer is 0.1 to 2 mm.
7. The positive electrode sheet according to claim 1, characterized in that: The thickness of the second active material layer is 0.1 to 2 mm.
8. The positive electrode sheet according to claim 1, characterized in that: A first projection of the first active material layer in the thickness direction of the positive electrode current collector coincides with a second projection of the second active material layer in the thickness direction of the positive electrode current collector, and an area of the first projection is equal to an area of the second projection.
9. The positive electrode sheet according to claim 1, characterized in that: The first conductive agent and the second conductive agent independently include at least one of conductive carbon black, graphene, conductive graphite, conductive carbon tube, and conductive carbon fiber.
10. The positive electrode sheet according to claim 1, characterized in that: The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose.
11. The method for preparing the positive electrode sheet according to any one of claims 1 to 10, characterized in that: The steps include: S1, mixing a first active material, a first conductive agent, a binder, and a first solvent uniformly to obtain slurry A; The second active material, the second conductive agent and the second solvent are mixed uniformly to obtain slurry B1; the polymer and the third solvent are mixed, and heated and stirred to obtain a polymer solution; the slurry B1 and the polymer solution are mixed uniformly to obtain slurry B2; S2, coating the slurry A on the surface of the positive electrode current collector, and performing a first drying to obtain a pole piece composited with a first active material layer; The slurry B2 is coated on the surface of the electrode sheet composited with the first active material layer, and the positive electrode sheet is obtained after a second drying, a rolling press, and a third drying.
12. The preparation method according to claim 11, characterized in that: The temperature of the first drying is 80-120° C., and the time of the first drying is 1-3 hours.
13. The preparation method according to claim 11, characterized in that: The temperature of the second drying is 80-120° C., and the time of the second drying is 1-3 hours.
14. The preparation method according to claim 11, characterized in that: The temperature of the third drying is 80-120° C., and the time of the third drying is 20-30 hours.
15. A hybrid ion battery, characterized in that: The hybrid ion battery comprises the positive electrode sheet according to any one of claims 1 to 10, and / or the positive electrode sheet prepared by the preparation method according to any one of claims 11 to 14.
Citation Information
Patent Citations
Potassium ion battery positive electrode material, preparation method and potassium ion battery
CN113675394A
Preparation method of KLi3Fe(C2O4)3, battery positive electrode active material, battery and electric equipment
CN111349000A
Potassium ion-doped carbon-coated lithium-rich ternary positive electrode material as well as preparation method and application thereof
CN112786875A